Ivacaftor improves lung disease in patients with advanced CF carrying CFTR mutations that confer residual function. (September 2020) - Salvatore, Donatello; Terlizzi, Vito; Francalanci, Michela; Taccetti, Giovanni; Messore, Barbara; Biglia, Carlotta; Pisi, Giovanna; Calderazzo, Maria Adelaide; Caloiero, Mimma; Pizzamiglio, Giovanna; Majo, Fabio; Cresta, Federico; et al.
Abstract: Background: Ivacaftor is an innovative treatment for CF. Ivacaftor monotherapy in a phase III trial for patients with F508del and a residual function (RF) mutation showed improvement in lung function. We evaluated the effectiveness and safety of ivacaftor in patients with severe CF carrying RF mutations. Methods: Data were collected from Italian CF centers with patients enrolled in an ivacaftor compassionate use program. Data were collected 1 year before and 1 year after commencement of ivacaftor. Results: Twenty-six patients received ivacaftor. The mean [standard deviation (SD)] percent predicted FEV1 significantly increased from 33.9% (8.3) before treatment to 44.0% (10.7) after 12 months of treatment (p < 0.00001). The mean distance in the 6-min walking-test significantly improved from 458.2 (110.5) m at baseline to 524.8 (91.9) m after 12 months (p < 0.00001). The overall number of days of antibiotic therapy decreased from 1693 during the year before ivacaftor to 714 in the year following ivacaftor, and the number of days of intravenous antibiotic treatment dropped from 714 to 88; both results were statistically significant (p < 0.00001). Patients needing intravenous therapy decreased from 23 to 5 of 26. The mean (SD) sweat chloride level decreased from a baseline of 79 (22.3) mmol/L to 65 (30.6) mmol/L, but this variation was not significant (p = 0.26). No safety concerns were registered. Conclusions: In patients with CFTR mutations that confer RF with severe lung disease, treatment with Ivacaftor is safe and results in a clinically significant improvement that was evident at 1 month and maintained at 12 months. Highlights: CF patients with residual-function (RF) CFTR mutations can suffer severe lung disease. Ivacaftor is safe and effective in severe patients with RF CFTR mutations. Ivacaftor decreases PEx and use of antibiotics in severe CF with RF mutations.